Derivative sinhx*tanhx

May 2010
129
0
WI - USA
When I calculate the derivative of

\(\displaystyle
y = sinh(x) tanh(x)
\)

I come up with

\(\displaystyle
y' = cosh(x) tanh(x) + sinh(x) sech^2(x)
\)

Should this be further simplified?
 
Jan 2010
564
242
Kuwait
\(\displaystyle cosh(x) \cdot tanh(x)=sinh(x)\)

then take \(\displaystyle sinh(x)\) as a common factor ..
 
  • Like
Reactions: Unknown008
May 2010
129
0
WI - USA
So...

\(\displaystyle
y' = sinh(x)(1+sech^2(x))
\)

Sorry, it has been a very long time since I have had to work these sorts of problems.